Psychometric properties of the Hindi version of Geriatric depression scale (HGDS) - jee, S.Gopal (IJRDO-Journal of Applied Science, 2016)
The present study reports the Hindi version of the Geriatric depression scale (GDS) and itspsychometric properties. The Hindi version of the GDS was developed following the contemporarymethodology of cross-cultural adaptation of psychometric tools. The Geriatric depression scale, TheBrief Assessment Schedule Depression Cards (BASDEC) and Mini Mental Status Examination wereadministered on a sample of 176 elderly in the age range of 60 to 90 years. The data were analyzed andtested on the basis of traditional test theory. The cross language equivalence of Hindi version of GDSwas ascertained by back translation method. Findings revealed a satisfactory subscale to totalcorrelation as well as satisfactory reliability (Internal consistency assessed by Chrobach’s alpha was0.74). For ascertaining the convergent validity coefficient of HGDS, two criterion measure such asBrief assessment schedule card (BASDEC) and Hindi version of Mini Mental Status Examination(HMMS) were taken and found to be significant correlation between them. The findings suggest that theHGDS is a reliable and valid tool for evaluation of depression in elderly population. The HGDSprovide a quick assessment of depression in elderly person and total score of this test reflects thegloomy mood in geriatric population.